The Application of Mutual Cooperation on the Social Development of Children Aged 5-6 Years - Sari, Mulya; Julisti, Vivi; Putri, Zikra Dwi; Sameto, Mayang Belia (Ahlussunnah: Journal of Islamic Education, 2025)
The purpose of this study was to understand the social aspects of children aged 5-6 years and to find out how the concept of mutual cooperation is implemented in children's social development. The method applied in this study is a qualitative method. This study aims to collect information on whether the values ​​of mutual cooperation have been applied in children's social development. In this study, there are two main focuses examined, namely: i) Social development of children aged 5-6 years. ii) Implementation of mutual cooperation in the social development of children aged 5-6 years. The results of the study indicate that the social development of children aged 5-6 years is in accordance with the appropriate stage of social development, including compliance with rules, the ability to interact with friends, and understanding in expressing good and bad behavior. Children aged 5-6 years can be said to have achieved significant social development. It is hoped that this development will enable children to socialize with friends and the environment and be able to work together in class groups. The implementation of mutual cooperation carried out by children includes activities such as maintaining the cleanliness of the schoolyard, pulling weeds, tidying up toys after use, and organizing and cleaning equipment after activities. Based on the results found, the implementation of mutual cooperation has been proven to stimulate children's social development.